Simulasi Pencahayaan Buatan untuk Ruang Kelas dengan Tipe Armature TL LED dan Bohlam LED - Hangga, Arimaz; Nisa, Alim Muanifatin; Pratama, Dewangga; Apriliyanto, Muchlisin (Jurnal Teknik Elektro, 2019)
Classroom light intensity is one of the essential factors in the learning process. Several factors affect light intensity in the classroom, i.e., determination of classroom design, position of objects in the classroom, window design, shading devices, type of lamp, and type of lamp armature. The research aims to determine the effect of armature lamp type. The results of this research are expected to increase the efficiency of electricity costs and use the classroom optimal lighting system according to Indonesian National Standard (SNI). Two types of lamp armature used in this research i.e. LED tube armature and LED bulb armature. This research used E11-210 classroom in E11 Building of Electrical Engineering Department, Universitas Negeri Semarang with the size of 12m x 9m x 3.5m. Simulation in this research used Dialux Evo 9 software. The results of observations and simulations show that E11-210 classroom had not followed SNI yet, in 350 lux. Based on simulation results, it shows that using LED tube armature and LED bulb armature will get light intensity of E11-210 classroom that follow SNI 6197:2011. Simulation results show that the use of LED tube armature (Powerbalance Gen2 RC463B) in E11-210 classroom will increase efficiency of electricity costs by 27.81%. Meanwhile, the use of LED bulb armature (Luxspace Ace Acccent RS750B) in E11-210 classroom will increase efficiency of electricity costs by 33.96%.